Formulation of Hydrogel Beads to Improve the Bioaccessibility of Bioactive Compounds from Goldenberry and Purple Passion Fruit and Evaluation of Their Antiproliferative Effects on Human Colorectal Carcinoma Cells - Ana María Naranjo-Durán; Diego Miedes; Juan Manuel Patiño-Osorio; Antonio Cilla; Amparo Alegría; Catalina Marín-Echeverri; Julián Quintero-Quiroz; Gelmy Luz Ciro-Gómez (Gels)
Goldenberry and purple passion fruit contain bioactive compounds (BCs) that can prevent gastrointestinal cancers; hydrogel beads can protect and control their release in the gastrointestinal tract. This study aimed to develop an encapsulating material for fruit hydrogel beads (FHBs) to increase their bioaccessibility and to assess antiproliferative effects. A blend of goldenberry–purple passion fruit was encapsulated using ionic gelation and electrospraying. Through a mixture experimental design with sodium alginate (SA), hydroxypropylmethylcellulose (HPMC) and arabic gum (AG) as components, the following response variables were optimized: polyphenol bioaccessibility and encapsulation efficiency. Polyphenols and antioxidant activity were quantified before and after digestion. Antiproliferative effect was evaluated on Caco-2 colon cancer cells. Variations in formulation proportions had a significant effect (p < 0.05) on most responses. An SA-AG mixture in a 0.75:0.25 ratio maximized polyphenol bioaccessibility to 213.17 ± 19.57% and encapsulation efficiency to 89.46 ± 6.64%. Polyphenols and antioxidant activity were lower in FHBs than in the fruit blend (F). Both F and FHBs inhibited tumor cell proliferation by 17% and 25%, respectively. In conclusion, encapsulating BCs in hydrogel beads with SA-AG can enhance the effectiveness of polyphenols in food applications by improving their bioaccessibility and showing a more pronounced effect in inhibiting tumor cell proliferation.